Novi režim načrtovanja dedovanja s čezmejnim elementom - Ivanc, Tjaša (Podjetje in delo, 2016)
For the Member States regulation with a connecting factor (habitual residence) and determination of the jurisdiction of one court, of whatever kind the assets in the estate may be, movable or immovable property, undoubtedly represents a fundamental change compared with the different conflict of laws rules in the Member States. The author also deals with the procedure for recognition and declaration of enforceability of foreign judgments, since the field of inheritance is excluded from the scope of the Brussels Regulation. The automatic recognition regime of the foreign judgment and the exequatur procedure should not cause major problems, since it was modelled on the Brussels Regulation. The Succession regulation maintained the special procedure, notwithstanding of the trend towards the elimination of the exequatur. Another novelty is Chapter V of the Succession Regulation, which is, compared to other EU instruments, original in its regulation on cross-border movement of authentic documents.
Keywords: dedno pravo; dedovanje; Evropska unija; izvršba; sodišča; sodne odločbe